Canada : Financial Sector Assessment Program-Crisis Management and Bank Resolution Framework-Technical Note. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This report underlies Canada's Financial Sector Assessment Program (FSAP) in the areas of crisis management and blank resolution. The provincial deposit insurance systems (DIS) and resolution frameworks are highly heterogeneous and the FSAP's analysis suggests that the preparedness to overcome financial stress should be enhanced. The IMF report discusses that the federal legal and institutional arrangements for resolving individual financial institutions are robust. It suggests that clear mandates should be assigned to: (1) monitor systematic risk to facilitate macroprudential oversight; and (2) carry out system wide crisis preparedness.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet